EVALUATION OF DRAINAGE WATER QUALITY FOR REUSE - A CASE STUDY OF THE UMOUM DRAIN IN EGYPT - Hossam M. Nagy; Adel A. S. Salem (Lowland Technology International, 2003)
Water resources in Egypt, being fixed in quantity, are under heavy pressure due to a continuously increasingpopulation. As such, reuse of drainage water for irrigation is an attractive proposition and is possible if the drainage water is of satisfactory quality. The Umoum Drain, one of the largest drains in the West Delta region, receives more than one billion cubic meters per year of agricultural drainage water. Moreover, the drain receives both raw and treated wastewater from several defined and undefined sources. In this study, the quality of the drain water was investigated. Flow and water quality profiles have been estimated along the drain through the mathematical model, QUAL2E. The model is used for calibratingthe deoxygenation rate in the drain by utilizing measured field data reported by the Drainage Research Institute (DRI), National Water Research Center in Egypt. The study concentrated on two nonconservative constituents: biochemical oxygendemand, BOD5, and dissolved oxygen, DO, and one conservative constituent representing the water salinity in terms of total dissolved solids, TDS. A parametric study is presented to investigate the effects of the deoxygenation rate on the values of BOD5, and DO concentrations in drainage water. A dynamic management strategy is presented as part of the scheme for improving water quality before discharge into the irrigation network. Primary treatment wastewater plants are proposed in specific locations along the drain. The study presents a design chart identifying the optimal amount of fresh water needed for the dilution of drainage water.